Military Coups as a Negation of Social Revolutions: the Nigerian Experience - Enor, Frank; Ebaye, Sunday E. N. (Mediterranean Journal of Social Sciences, 2011)
The military in Nigeria has dominated the socio-political landscape of the country for more than thirty years sporadically.Within these years, the military had executed far reaching reforms and policies in the socio-economic and political substructures of thenational economy. Although the military had made some progress in areas where civilian administration had failed, military incursioninto politics still negates a populist social revolution, thus failed to institute a genuine democratic culture in the country. This paperattempts an examination of military adventurism from the backdrop of revolutionary pressures in Nigeria and contends that suchinterventions foreclosed the chances of structural change by the people. The paper concludes that a social revolution is a fundamentalapproach to a genuine democratic culture in Nigeria.